Educational Puzzle Game of Tourism Object Using Random Shuffle Algorithm: Game Edukasi Puzzle Pengenalan Objek Wisata Menggunakan Algoritma Shuffle Random - Potu, Gabriely; Sompie, Sherwin R. U. A.; Kaunang, S. T. G. (Universitas Sam Ratulangi, 2024)
The development of technology is currently growing very rapidly, therefore the current use is not only used by adults, but the technology is already used by children. The development of increasingly modern technology makes children choose new things. Therefore, many children today do not know about tourist attractions in North Sulawesi. As time goes by, the need for technology is increasing, the goal is for learning and entertainment. One of the existing learning and entertainment media for technology development is puzzle games. With puzzle games can be used as a medium to communicate various types of information, such as presenting the introduction of tourist objects that aim to be able to create an educational game puzzle introduction to North Sulawesi attractions using the Random Shuffle Algorithm using the Multimedia Develompment Life Cycle (MDLC) development method. Based on the results of research and questionnaires, it can be concluded that this puzzle game can make one of the alternative media in the introduction of North Sulawesi tourism objects.